PENYELARASAN KURIKULUM SMK KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF DENGAN KOMPETENSI INDUSTRI - Andhika Cahya Mahendra; Ranto Ranto; Towip Towip (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The development of this fast era makes competition to get a job to increase and become more difficult. In the current competition in the industrial world, it demands an increase in the quality of Human Resources through education. Vocational High School Education also prepares its graduates to go directly into the world of industry, but there are still limitations between the need for human resources in industry and the human resources produced by educational institutions. So therefore Curriculum development in Vocational High Schools is developed by prioritizing the needs of society, one of which is the need to be able to compete directly in industry. The aims of this research are: (1) To find out the alignment process between the SMK curriculum and industry. (2) Knowing how far the curriculum in SMK is aligned with the world of work in industry. (3) Knowing whether the SMK curriculum with industry is feasible.  The method used in the automotive concentration curriculum alignment activities at SMKs uses a qualitative approach with descriptive research. Data collection techniques using techniquespupose sampling. Data collection techniques in this study used data collection techniques in the form of interviews, documents, and observations. The research documents include the Merdeka Curriculum, K13 Curriculum, service books, vehicle inspection sheets, and the results of the FGD minutes. Data analysis techniques in this study used content analysis techniques (analysis content). The research locations were limited to 2 SMK, namely: SMKN 2 Surakarta and SMK Warga Surakarta and three industries, namely: Toyota Nasmoco Ringroad, Daihatsu Adi Sucipto, and Suzuki Pabelan (PT. Solo Indonesia Utama). The data obtained is then juxtaposed between the curriculum and competencies in the industry in tabular form so that it can be seen which curriculum and competencies are not aligned. The results of this study are: The curriculum between automotive engineering vocational schools and industrial competencies is aligned, this is evidenced by the existenceforum grub discussion (FGD) between the SMK and the automotive industry.